The incorporation of Mg2+ ions into aragonite during biomineralization: Implications for the dolomitization of aragonite - Han, Zuozhen; Meng, Ruirui; Zhao, Hui; Gao, Xiao; Zhao, Yanyang; Han, Yu; Liu, Fang; Tucker, Maurice E.; Deng, Jiarong; Yan, Huaxiao (Frontiers in Microbiology, 2023)
In our laboratory experiments, the content of Mg2+ ions in biotic aragonite is higher than that in inorganically-precipitated aragonite and we hypothesize that the higher Mg content may enhance the subsequent dolomitization of aragonite. The molecular mechanisms of the incorporation of Mg2+ into aragonite facilitated by bacteria are still unclear and the dolomitization of aragonite grains is rarely reported. In this study, biotic aragonite was induced by Bacillus licheniformis Y1 at different Mg/Ca molar ratios. XRD spectra show that only aragonite was precipitated in the media with Mg/Ca molar ratios at 6, 9 and 12 after culturing for 25 days. The EDS and atomic absorption results show that the content of Mg2+ ions in biotic aragonite increased with rising of Mg/Ca molar ratios. In addition, our analyses show that the EPS from the bacteria and the organics extracted from the interior of the biotic aragonite contain the same biomolecules, including Ala, Gly, Glu and hexadecanoic acid. The content of Mg2+ ions in the aragonite precipitates mediated by biomolecules is significantly higher than that in the inorganically-precipitated aragonite. Additionally, compared with Ala and Gly, the increase of the Mg2+ ions content in aragonite promoted by Glu and hexadecanoic acid is more effective. The DFT calculations reveal that the energy needed for Mg2+ ions incorporation into aragonite mediated by Glu, hexadecanoic acid, Gly and Ala increased gradually, but was lower than that without acidic biomolecules. The experiments also show that the Mg2+ ions content in the aragonite significantly increased with the increasing concentration of biomolecules. The dolomite could be detected after the dolomitization of the biotic aragonite. This study may provide new insights for understanding the important role played by biomolecules in the Mg2+ ion incorporation into aragonite. Moreover, these experiments may help understand the dolomitization of aragonite better.